(untitled) (Palíndromo, 2024)
Tragedy can take on several dimensions in the same story, depending on our understanding. This article seeks to develop a reflection on the visual fortune of the different tragic layers in the story of Castellan de Vergy (written in the first half of the 13th century), which narrated the love of a young couple and the deaths of three of the four characters. The wide circulation of the novel stimulated the production of images on different media. Based on the analysis of a miniature, a metal insignia, an ivory casket and a fresco, this study will address how the episodes represented related both to the novel and dialogued with the community, impacting the construction of relationships within the Pre Modern Societies.